(untitled) (Central Asian Journal of Medical Sciences, 2024)
Objective: The objective of this study was to assess the determinants of attitude towards depression and suicidal ideation among postpartum women in Southern Nigeria. Methods: An analytical cross-sectional study using interviewer-administered structured questionnaires involved 480 mothers attending the postnatal clinics at the University of Benin Teaching Hospital, Benin City, Edo State. Data collected was analyzed using SPSS version 25. 0 statistical software with statistical significance set at P < 0.050. Results: The mean age of respondents studied was 31.3 ± 5.7 years. Four hundred and forty-four (92.5%) and 36 (7.5%) respondents had negative and positive attitudes towards depression and suicidal ideation, respectively. Age (OR = 0.809; 95%CI = 0.725 – 0.905; P <0.001), marriage type (OR = 0.177; 95% CI = 0.045 – 0.696; P = 0.013), and skill level (OR = 30.240; 95% CI = 2.991 – 305.78; P = 0.004) of respondents were significant predictors of positive attitude. Conclusion: The majority of respondents studied had negative attitudes towards depression and suicidal ideation. Women should be encouraged to seek professional help when they notice symptoms and signs suggestive of depression and suicidal ideation.